2017
DOI: 10.2174/2352633501703010016
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Chemical Composition of Two Essential Oils and Eugenol from Flower Buds of

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…These reported phenotypes were coherent with our findings. The positive strain Staphylococcus aureus has the lowest sensitivity toward the films' cloves oil components, especially eugenol, which is the main factor inhibiting fungal activity due of the lyses of spores and micelles [70,71].…”
Section: Free Radical Scavenging Activitymentioning
confidence: 99%
“…These reported phenotypes were coherent with our findings. The positive strain Staphylococcus aureus has the lowest sensitivity toward the films' cloves oil components, especially eugenol, which is the main factor inhibiting fungal activity due of the lyses of spores and micelles [70,71].…”
Section: Free Radical Scavenging Activitymentioning
confidence: 99%
“…Studies have shown that clove essential oil is effective in reducing the microbial load of hatching eggshells, provides good results in terms of incubation performance, and improves the quality of neonate chicks [3,12]. This oil is an aromatic hydrophobic extract of Syzygium aromaticum (family: Myrtaceae) and is mainly composed of phenylpropanoids, such as eugenol (C 10 H 12 O 2 ), which constitutes 90% of the oil and is the main compound responsible for its antimicrobial activity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are in agreement with those obtained previously in cultivated cloves. Cultivated cloves produce the highest oil content in the flower part, which is around 10-20%, then followed by flower stalks around 5-10%, and the lowest is the leaves which is <5% (Nurdjannah, 2004;Widayat et al, 2014;Atanasova-Pancevska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%